A case study analysis of a constructionist knowledge building community with activity theory - Ang, Chee Siang; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2011)
This article investigates how activity theory can help research a constructionist community. We present a constructionist activity model called CONstructionism Through ACtivity Theory (CONTACT) model and explain how it can be used to analyse the constructionist activity in knowledge building communities. We then illustrate the model through its application to analysing the Wiki-supported community associated with a computer game. Our analysis focuses mainly on two perspectives: individual and collective actions, as well as individual and collective mediations. Experiences and challenges from the analysis are reported to demonstrate how CONTACT is helpful in analysing such communities.
Keywords: Activity theory; Constructionism; Game community; Knowledge building; Wiki